2021
DOI: 10.21608/bjas.2021.169595
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Calprotectin Level in Patients with Acne Vulgaris and its Correlation to Disease Severity

Abstract: Acne vulgaris is a common skin condition that affects people all over the world. Acne vulgaris is characterised by the presence of open and closed comedones, papules, pustules, and nodules on areas of the body with hormonally sensitive sebaceous glands. Acne is thought to be caused by four key factors: increased sebum production, follicular hyperkeratinization, skin bacterial colonisation, and inflammation. Acne with severe symptoms is painful, disfiguring, scarring, and lowering self-esteem. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Abd Allah et al (19) findings, on the other hand, revealed no important connection between calprotectin serum levels and the length of AV in their patients. This contrasted with the findings of Fouda et al (21) , who discovered a strong positive association between serum calprotectin levels and acne duration(r =0.247; P =0.057).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Abd Allah et al (19) findings, on the other hand, revealed no important connection between calprotectin serum levels and the length of AV in their patients. This contrasted with the findings of Fouda et al (21) , who discovered a strong positive association between serum calprotectin levels and acne duration(r =0.247; P =0.057).…”
Section: Discussionmentioning
confidence: 64%
“…This was in line with Fouda et al (21) who reported similar results. Similarly, the amount of serum calprotectin was found to have a strongly important positive association with GAGS score (r=0.854; P <0.001) in Abd Allah et al (19) study. In a study conducted by Korkmaz and Fçcolu (1) , it was shown that the serum calprotectin levels of people with moderate-severe AV were statistically substantially greater than those of people with mild AV (P <0.001).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations